Desempenho de linhas de transmissão HVDC frente a descargas atmosféricas: aspectos de interesse e análises de sensibilidade - Amanda Andreatta Campolina Moraes (2024)
This work aims to present a contribution referred to the lightning performance of HVDC, High Voltage Direct Current, transmission lines considering backflashover. A set of sensitivity analysis is developed based on computational simulations, considering different line topologies and position of the DC poles, a wide range of grounding impulse impedances, Zp, and assuming the incidence at the tower top of negative and positive lightning. This work also compares the performance of HVDC and HVAC lines with the same tower configuration and voltage level. The work presents a discussion of the influence of the polarity and position of the DC poles, or phase conductors on the resulting overvoltages across line insulator strings, critical currents and probability of backflashover occurrence, for two HVDC transmission line configurations, that considers a self-supporting double circuit 500 kV tower and a guyed 600 kV single circuit tower. These analyzes were carried out with the assistance of computational simulations based on the HEM model, Hybrid Electromagnetic Model, and the progression model from the LPM, Leader Progression Model. The study highlights the importance of the positioning and polarity of the poles and the value of the tower footing impedance for defining the performance of HVDC lines. The results indicate, in general, the worst performance (lower values of critical current) for negative lightning when the positive poles are positioned in the lower insulator strings of the self-supported HVDC transmission tower. On the other hand, the worst performance assuming positive lightning is related to negative poles positioned in the lower insulator strings. Similar behaviour is observed for the transmission line with guyed tower, as expected. Also, the worst performances are observed for greater values of tower-footing impedance for both line configurations. Furthermore, a better general lightning performance was noted for the guyed tower, 600 kV, in comparison with the one for the self-supporting tower, 500 kV, in addition to a better performance of both towers for the case of negative lightning, and the apparent worse performance of the HVDC system compared to the HVAC system, both with the same tower topology and voltage level. The worst performance for the HVDC system is indicated through the analysis of critical current, probability of backflashover occurrence and outage rate. Maximum Zp values were calculated to achieve the performance of 1 outage/100 km/year, determined by ONS, National System Operator of Brazil, for extra-high voltage transmission lines. These limit values are lower for the HVDC system, indicating its worse performance and the need to install longer counterpoise wires for the same soil conditions.